Heterogeneity in Body Contouring Outcomes Based Research: The Pittsburgh Body Contouring Complication Reporting System. (15th June 2017) - Guest, Rachel A; Amar, Dalit; Czerniak, Sharona; Dreifuss, Stephanie E; Schusterman, Mark A; Kenny, Elizabeth M; Chernoff, Eva F; Barnett, Joshua M; Koesarie, Kathleen R; Gusenoff, Jeffrey A
Abstract: Background: Body contouring complications after massive weight loss (MWL) vary significantly in frequency and type. Currently, no standardized recommendations exist regarding which complications are most important to report. Objectives: We aim to provide a guideline for complication reporting in the body contouring literature. The Pittsburgh Body Contouring Complication Reporting System (PBCCRS) will aid in risk stratification of body contouring procedures and will decrease under-, over-, and nonreporting of complications. Methods: The authors reviewed the literature for the terms "body contouring, " "MWL, " and "complications." Elimination criteria included: non-English language, case report, meta-analysis, outpatient, non-MWL, unclear demographics, N <30 and lack of numeric results. Data were analyzed in 2 groups: truncal contouring and extremity contouring. Results: Eighty-nine papers were reviewed and 21 met inclusion criteria. The weighted mean rates as percentages for complications in the extremity group were: dehiscence (29.0), seroma (18.6), scarring (14.9), infection (8.8), lymphedema (7.8), hematoma (3.5), necrosis (1.9), deep venous thrombosis (DVT) or pulmonary embolism (PE) (0), and death (0). In the truncal group, weighted mean complication rates as percentages were: dehiscence (15.4), seroma (13.1), scarring (2.9), infection (9.4), lymphedema (1.3), hematoma (6.4), necrosis (7.2), DVT/PE (1.5), and death (0.6). Lymphedema was seldom reported, and suture extrusion was not reported in any selected papers. Weighted mean rates of DVT/PE in the extremity vs truncal contouring groups were significantly different. Differences in rates of scarring, lymphedema, and hematoma rates neared significance. Conclusions: Heterogeneity amongst selected studies is explained by variability in how complications are defined. The Pittsburgh Body Contouring Complication Reporting System provides suggested recommendations on complication reporting in massive weight loss body contouring surgery.